Hubungan Antara Implementasi Corporate Social Responsibility Dengan Kinerja Perusahaan Studi Terhadap Perusahaan Yang lIsted di Bursa Efek Indonesia Sejak Tahun 2006-2008 - , Mohammad Irvan, SE., Dr. Khomsiah, MM. Ak ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The thesis is focus on finding relation between Corporate Social Responsibility (CSR) and companyâs performance. The CSR implementation applied is refer to Global Reporting Initiative Index. Other than, the Companyâs performance is reflected by Return on Assets (ROA), Net Profit Margin (NPM) and Total Assets Turn Over (TATO) This thesis use companies listed in Indonesia Stock Exchange from 2006- 2008, use sustainability report presented in annual report. This thesis use correlation examination to get understanding of the relationship between CSR implementation and companyâs performance. In addition, to get more understanding, this thesis use double regression to examine companyâs performance influences to CSR. From the examination, it is found that CSR which have relationship with companyâs performance are economic activity, employee conduct, and product responsibility. These implementations have positive relationship with ROA. In addition, it is found that employees conduct and environment are the most activities done by companies. It also found that companyâs profiles has relationship and influences to CSR implementations. But this relationship has negative relationship.